The growth of participant direction in defined contribution plans - William E. Even; David A. Macpherson (Institute for the Study of Labor (IZA), 2009)
Since 1990, most pension plans have shifted the responsibility for directing pension assets to the employee. This study summarizes some of the possible explanations for this rapid shift toward participant direction and uses IRS Form 5500 data to investigate the effect of worker and plan characteristics on the likelihood of making a switch. The study also estimates the effect of a switch to participant direction on employee contribution and asset allocation behavior. The analysis reveals that collective bargaining and pension investments in employer stock reduce the chance of a switch to participant direction, whereas below average return performance increases the chance. Also, a switch to participant direction increases employee contributions to the pension and reduces the share of assets invested in employer securities.
urn:nbn:de:101:1-20090330256
Keywords: J32; 330; Participant direction; pensions; employer stock; Betriebliche Altersversorgung; Pensionsfonds; Arbeitnehmerbeteiligung; Anlageverhalten; USA